Principles of Financial Accounting - Chiappetta Barbara; Larson Kermit D.; Wild John J. (New York : McGraw -Hill, 2003)
Book Description
Fundamental Accounting Principles, Fourteenth Edition, is the most-customer-driven revision in Fundamentals history. Surveys, focus groups, reviewers, and personal correspondence pointed the way to the trends in the introductory accounting market: the demand for a business orientation, the need to find new ways to motivate students, the need for flexibility and innovation in the classroom, new pedagogy, and the impact of technology. Reflecting these needs and the changes recommended by the Accounting Education Change Commission, Larson and Chiappetta have aggressively integrated real-company examples; made the topical presentation relevant and interesting to all business majors; developed innovative pedagogy; included challenging, new end-of-chapter material; and developed technological innovations for both instructors and students. The new modern principles course is supported by exciting changes in the text and supplement package. --This text refers to an out of print or unavailable edition of this title.
Book Info
The most customer-driven revision in Fundamentals history. The new modern principles course is supported by exciting changes in the text and includes a supplement package. --This text refers to the Hardcover edition.
Keywords: Financial Accounting; Tài chính kế toán